Association of hemoglobin, albumin, lymphocyte, and platelet score with risk of all-cause and cause-specific mortality among cancer survivors: NHANES 1999-2018 - Fu, Jixin; Yue, Xiaohan; Zou, Yanan; Zhang, Jian (Frontiers in Oncology, 2024)
BackgroundThe HALP score, comprising hemoglobin, albumin, lymphocyte, and platelet levels, serves as an indicator of both nutritional and inflammatory status. However, its correlation with all-cause and cause-specific mortality among cancer survivors remains unclear. Therefore, this study aims to investigate the relationship between HALP scores and mortality outcomes in this population.MethodWe extracted cohort data spanning ten cycles (1999-2018) from the U.S. National Health and Nutrition Examination Survey (NHANES). Mortality rates, determined using the National Death Index (NDI) as of December 31, 2019, were assessed. Weighted multivariate logistic regression analyzed the association between HALP scores and cancer prevalence. Kaplan-Meier analyses and weighted multivariate-adjusted Cox analyses investigated the link between HALP scores and all-cause and cause-specific mortality in cancer survivors. Restricted cubic spline (RCS) analysis was employed to assess nonlinear relationships. Furthermore, multi-parametric subgroup analyses were conducted to ensure the robustness of the results.ResultsOur study included 41,231 participants, of whom 3,786 were cancer survivors (prevalence: 9.5%). Over a median follow-up of 91 months (range: 51-136), we observed 1,339 deaths, including 397 from cancer, 368 from cardio-cerebrovascular disease, and 105 from respiratory disease. Elevated HALP scores showed a consistent association with reduced cancer incidence (P for trend <0.001). In multivariable-adjusted Cox regression analyses, HALP scores were significantly inversely associated with all-cause mortality, cancer mortality, cardio-cerebrovascular disease mortality, and respiratory disease mortality in cancer survivors (P for trend < 0.05). Nonlinear relationships between HALP scores and all-cause and cause-specific mortality in cancer survivors were evident through RCS regression modeling (P for nonlinearity < 0.01). Kaplan-Meier analyses demonstrated that higher HALP scores were indicative of a poorer prognosis.ConclusionOur findings indicate a notable inverse correlation between HALP scores and both all-cause and cause-specific mortality among cancer survivors.